Venous Thrombosis, Oral Contraceptives and High Factor VIII Levels - Bloemenkamp, K. W. M.; Helmerhorst, F. M.; Rosendaal, F. R.; Vandenbroucke, J. P. (Thrombosis and Haemostasis, 1999)
Recently, it has been described that elevated plasma levels of factor VIII are a strong risk factor for venous thrombosis. We analysed the data of the Leiden Thrombophilia Study, a population based case-control study on the causes of venous thrombosis, to verify whether the risk due to oral contraceptive use was higher in women with higher factor VIII levels. Furthermore we investigated the joint risk of high factor VIII levels and oral contraceptive use.We selected 155 premenopausal women with deep-vein thrombosis and 169 control subjects, aged 15-49, who were at the time of their thrombosis (or similar date in control) not pregnant, nor in the puerperium, did not have a recent miscarriage, and were not using injectable progestogens. Of the patients, 109 (70%) women had used oral contraceptives during the month preceding their deep-vein thrombosis, in contrast to 65 (38%) of the control subjects (index date), yielding an odds ratio for oral contraceptive use of 3.8 (95% CI 2.4-6.0). Of the women who suffered a deep-vein thrombosis 56 (36%) had high factor VIII levels (≥150 IU/dl) as compared with 29 (17%) of the control subjects, yielding an odds ratio for high factor VIII of 4.0 (95% CI 2.0-8.0), relative to factor VIII levels <100 IU/dl. The joint effect of oral contraceptive use and high factor VIII resulted in an odds ratio of 10.3 (95% CI 3.7-28.9), comparing women who had both with women who had neither. We conclude that there is an increase in risk due to oral contraceptive use in women with higher factor VIII levels and that both factors have additive effects.